The establishment of a Lidar facility at Rhodes University - Grant, Richard Peter James Seton (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1988)
LIDAR is the optical equivalent of RADAR. A LIDAR facility has been established at Rhodes University using a flashlamp-pumped dye laser as the transmitter and a photomultiplier tube at the focus of a searchlight mirror as the receiver. The setting up of the receiver and transmitter as well as the design and construction of the photon counting electronics is described. The LIDAR has been used to measure aerosol scattering ratios and temperature profiles in the stratosphere and these results are presented with the algorithms and software used to reduce the data. Finally some recommendations are made for future work
Keywords: Optical radar; LIDAR; Receiver; Transmitter; Photon counting electronics; Aerosol scattering; Temperature profiles; Stratosphere